2021
DOI: 10.4103/ijo.ijo_3401_20
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal electroretinography-assisted anatomical and functional evaluation of subthreshold green laser in acute central serous chorioretinopathy

Abstract: Purpose: To compare observation versus subthreshold green laser (STL) in acute central serous chorioretinopathy (CSC) in terms of anatomical and functional outcomes. Methods: Prospective randomized interventional study. 30 eyes with the first episode of acute CSC underwent complete ophthalmologic examination, measurement of best-corrected Snellen visual acuity (BCVA), contrast sensitivity (CS), fundus fluorescein angiography (FFA), spectral-domain optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Moreover, different duty cycles were used, usually ranging from 5 to 15% [ 13 ]. In some studies, only the area with focal leakage, as seen on angiography, was treated [ 20 ], while in others, all areas under the neurosensory detachment were treated [ 18 ]. We believe that the SML treatment effect is in improving the RPE pump capacity; therefore, we treated our patients with high-density laser spots under the area of neurosensory detachment without sparing the fovea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, different duty cycles were used, usually ranging from 5 to 15% [ 13 ]. In some studies, only the area with focal leakage, as seen on angiography, was treated [ 20 ], while in others, all areas under the neurosensory detachment were treated [ 18 ]. We believe that the SML treatment effect is in improving the RPE pump capacity; therefore, we treated our patients with high-density laser spots under the area of neurosensory detachment without sparing the fovea.…”
Section: Discussionmentioning
confidence: 99%
“…Patients in the SML treatment group had better BCVA [ 19 ] and CS [ 18 , 19 ] outcomes. Moreover, a study comparing mfERG amplitudes and implicit times in acute CSC patients with or without SML treatment showed improved amplitudes in the first and second rings in the treated group at 3 and 6 months [ 20 ]. The SML treatment strategy in this study was treatment to the leakage site only [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another limitation of this study is the relatively small number of patients receiving treatment as well as the limited number of treatments received. Previous studies have reported that different types of treatment rendered different results in the functional examination [23][24][25], which means that different types of treatment can lead to different mfERG outcomes. However, there are limitations to revealing the difference in the results of mfERG according to the type of treatment due to the insufficient number of patients and types of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The SRF accumulation in acute CSCR causes photoreceptor damage, which is persistent and manifests as decreased contrast sensitivity, micropsia, persistent scotomas even after SRF resolution. [ 7 8 ] Chronic CSCR has a poor long-term visual prognosis due to accompanying RPE atrophy and persistent NSD. [ 8 9 ] Hence, it is crucial to treat CSCR in the acute phase.…”
mentioning
confidence: 99%
“…[ 7 8 ] Chronic CSCR has a poor long-term visual prognosis due to accompanying RPE atrophy and persistent NSD. [ 8 9 ] Hence, it is crucial to treat CSCR in the acute phase.…”
mentioning
confidence: 99%